A newly synthesized compound, 4′‐geranyloxyferulic acid–N(omega)‐nitro‐l‐arginine methyl ester suppresses inflammation‐associated colorectal carcinogenesis in male mice. Issue 4 (28th January 2014) - Shimizu, Masahito; Kochi, Takahiro; Shirakami, Yohei; Genovese, Salvatore; Epifano, Francesco; Fiorito, Serena; Mori, Takayuki; Tanaka, Takuji; Moriwaki, Hisataka
<x xml:space="preserve">Abstract</x> We previously reported the cancer chemopreventive activity of 4′‐geranyloxyferulic acid (GOFA, Miyamoto et al., Nutr Cancer 2008; 60:675‐84) and a β‐cyclodextrin inclusion compound of GOFA (Tanaka et al., Int J Cancer 2010; 126:830‐40) in colitis‐related colorectal carcinogenesis. In our study, the chemopreventive effects of a newly synthesized GOFA‐containing compound, GOFA–N(omega)‐nitro‐l‐arginine methyl ester (L‐NAME), which inhibits inducible nitric oxide (iNOS) and cyclooxygenase‐2 (COX) enzymes, were investigated using a colitis‐associated mouse colorectal carcinogenesis model with azoxymethane (AOM) and dextran sodium sulfate (DSS). The dietary administration of GOFA–L‐NAME after the AOM and DSS treatments significantly reduced the multiplicity of adenocarcinomas (inhibition rates: 100 ppm, 84%, p < 0.001; 500 ppm, 94%, p < 0.001) compared with the AOM + DSS group. Dietary GOFA–L‐NAME significantly decreased the proliferation (p < 0.001) and increased the apoptosis (p < 0.001) of colonic adenocarcinoma cells. A subsequent short‐term experiment revealed that dietary GOFA–L‐NAME decreased the mRNA expression of inflammatory enzymes, such as iNOS and COX‐2, and proinflammatory cytokines, such as tumor necrosis factor‐α, interleukin (IL)−1β, IL‐6 and macrophage inflammatory protein (MIP)−2 in the colonic mucosa of mice that received 1.5% DSS in their drinking water for 7 days. Our findings indicate that GOFA–L‐NAME is able to inhibit colitis‐associated colon carcinogenesis by modulating inflammation, proliferation, apoptosis and the expression of proinflammatory cytokines in mice.